2019
DOI: 10.5946/ce.2018.181
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Epithelial-Mesenchymal Transition Markers in Early Gastric Cancer: Cancer Tissue versus Noncancer Tissue

Abstract: Background/AimsEpithelial-mesenchymal transition (EMT) is a developmental process, wherein the epithelial cells show reduced intercellular adhesions and acquire migratory fibroblastic properties. EMT is associated with downregulation in epithelial marker expression, abnormal translocation of E-cadherin, and upregulation in mesenchymal marker expression. Here, we investigated the immunohistochemical (IHC) expression of EMT markers in early gastric cancer (EGC) between cancer and noncancer tissues. MethodsTissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…As regard E-Cadherin expression pattern, there was a statistically signi cant difference between chronic gastritis and GC cases with the lowest percentage of homogenous expression in GC cases. These ndings were consistent with others who suggest the role of E-Cadherin in multistep carcinogenesis [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…As regard E-Cadherin expression pattern, there was a statistically signi cant difference between chronic gastritis and GC cases with the lowest percentage of homogenous expression in GC cases. These ndings were consistent with others who suggest the role of E-Cadherin in multistep carcinogenesis [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, our preliminary results revealed a significantly higher value of α-SMA in CSCs subpopulation in comparison to parental cells. These results could be supported by previous studies on basal cell carcinoma, gastric, ovarian, and prostate cancer in which, the higher expression of α-SMA in malignant cells was significantly associated with increased tumorigenesis, migration, and invasion ability, indicating its possible role in CSC biology (Anggorowati et al, 2017;Jung et al, 2019;Jabour et al, 2022;Masola et al, 2022). A recent study by Jabour et al (2022) reported that the aggressive biological behavior of basal cell carcinoma can be predicted using α-SMA biomarker.…”
Section: Cd44 Positive Cancer Stem Cells Express Invasion and Metasta...supporting
confidence: 76%
“…Gastric cancer (GC) is a malignancy that occurs in gastric epithelial tissue [ 1 ], and its incidence accounts for 40%–50% of gastrointestinal cancers, ranking first in gastrointestinal tumors [ 2 ]. Additionally, its morbidity and mortality rank second among malignant tumors worldwide, and its morbidity and mortality rank first among all cancers in China [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%